A universal approach to prepare reagents for DNA-assisted protein analysis. - Junhong Yan; Gucci Jijuan Gu; Christian Jost; Maria Hammond; Andreas Plückthun; Ulf Landegren; Masood Kamali-Moghaddam (PLoS ONE, 2014)
The quality of DNA-labeled affinity probes is critical in DNA-assisted protein analyses, such as proximity ligation and extension assays, immuno-PCR, and immuno-rolling circle amplification reactions. Efficient, high-performance methods are therefore required for isolation of pure conjugates from reactions where DNA strands have been coupled to antibodies or recombinant affinity reagents. Here we describe a universal, scalable approach for preparing high-quality oligonucleotide-protein conjugates by sequentially removing any unconjugated affinity reagents and remaining free oligonucleotides from conjugation reactions. We applied the approach to generate high-quality probes using either antibodies or recombinant affinity reagents. The purified high-grade probes were used in proximity ligation assays in solution and in situ, demonstrating both augmented assay sensitivity and improved signal-to-noise ratios.